1997
DOI: 10.7863/jum.1997.16.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ultrasound characterization of the suprarenal mass: distinction between neuroblastoma and subdiaphragmatic extralobar pulmonary sequestration

Abstract: With the increased routine use of prenatal ultrasonography, subdiaphragmatic masses in the fetus are identified more frequently. Suprarenal masses often are presumed to be neuroblastoma and are removed surgically postnatally. We sought to better understand the natural history of subdiaphragmatic extralobar pulmonary sequestration, and to determine if subdiaphragmatic extralobar pulmonary sequestration can be distinguished preoperatively from neuroblastoma. The literature was reviewed for cases of prenatally di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 6 publications
1
44
0
5
Order By: Relevance
“…Differential diagnosis in right-sided masses includes hamartoma and hemorrhage, which more commonly arise diagnostic dilemmas when compared with left sided masses such as sequestration. Bilateral involvement of adrenal glands, cystic metastatic lesions in the liver, thickened walls, calcifications, cystic lesions with solid components and increased color-coding in Doppler US favors the diagnosis of NB [8][9][10]. Increased serum NSE is the major biochemical finding that supports the diagnosis of cystic NB.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Differential diagnosis in right-sided masses includes hamartoma and hemorrhage, which more commonly arise diagnostic dilemmas when compared with left sided masses such as sequestration. Bilateral involvement of adrenal glands, cystic metastatic lesions in the liver, thickened walls, calcifications, cystic lesions with solid components and increased color-coding in Doppler US favors the diagnosis of NB [8][9][10]. Increased serum NSE is the major biochemical finding that supports the diagnosis of cystic NB.…”
Section: Discussionmentioning
confidence: 82%
“…Haberal et al identified a case of a right sided-NB, which was misdiagnosed as infantile hemangioendothelioma of the liver that caused severe consumption coagulopathy and bleeding into the adrenal glands [9]. The differential diagnosis of left cystic adrenal NB includes extralobar sequestration, especially in the prenatal period [10]. Differential diagnosis in right-sided masses includes hamartoma and hemorrhage, which more commonly arise diagnostic dilemmas when compared with left sided masses such as sequestration.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 10% of extrapulmonary sequestrations are found intra-abdominally (IEPS), and 90% of IEPSs occur on the left side. 9,20,21 Intra-abdominal extralobar pulmonary sequestrations occur predominantly as sharply circumscribed masses in the left upper quadrant between the diaphragm and kidney, separated from the normal adrenal gland. Indeed, this is probably the most common left suprarenal mass detected in the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up sonography is clearly important. Curtis et al 21 presented a well-designed diagnostic and treatment algorithm for a prenatally detected suprarenal mass. A recent report of a 13-month-old boy with primary pulmonary rhabdomyosarcoma that originated within a CCAM illustrated the need for careful follow-up in cases of CCAM.…”
Section: Discussionmentioning
confidence: 99%
“…The major differential diagnosis of a prenatal/neonatal suprarenal mass includes adrenal hemorrhage and neuroblastoma (5). Adrenal hemorrhage may be echogenic when first detected but becomes hypoechoic or anechoic within several days or shrinks in the first month of life (6).…”
Section: Discussionmentioning
confidence: 99%